Assessment of Scholarly Publications of Nigerian Health Sciences Researchers in MEDLINE/PubMed (1996-2007) (2011)
Scholarly publications are outcome of research and are important channels for dissemination of research findings by researchers. The main objective of this study was to assess the scholarly publications of Nigerian health sciences’ researchers and the journals in which they publish. Health science researchers are health care providers, faculty, medical scientists and other allied health professionals who conduct research in health related fields. Research articles written by Nigerian health sciences’ researchers published during 1996-2007 were accessed through the MEDLINE/PubMed database. Both the author affiliation in Address field and Publication date field were used to obtain data on the number and characteristics of publications by the researchers. A total of 7030 articles were published during the period. The number of publications increased from 338 in 1996 to 952 in 2007. Of the 7,030 citations, 2,124 (31%) were published in nine Nigerian journals with the African Journal of Medicine and Medical Sciences having the highest (660). However, 17 articles were published in four international multidisciplinary journals namely: British Medical Journal (BMJ), Journal of the American Medical Association (JAMA), Lancet and New England Journal of Medicine (NEJM). Approximately 80% of the publications were Original Research Articles. Nigerian health sciences’ researchers are productive in terms of scholarly publications. However, their publications are concentrated more in national journals, some of which are not indexed in any bibliographic database; others are print only, not widely circulated thereby limiting the impact of their research. Development of a national bibliographc database to index articles published in Nigerian journals and publication of more journal in electronic format is recommended.